Diversity analysis and genetic potency identification of local rice cultivars in Penajam Paser Utara and Paser Districts, East Kalimantan - NURHASANAH NURHASANAH; SADARUDDIN SADARUDDIN; WIDI SUNARYO (Society for Indonesian Biodiversity, 2016)
Nurhasanah, Sadaruddin, Sunaryo W. 2016. Diversity analysis and genetic potency identification of local rice cultivars in Penajam Paser Utara and Paser Districts, East Kalimantan. Biodiversitas 17: 401-408. Local rice cultivars provide genetic diversity in rice genepool that is very useful for rice breeding programs. Less is known about local rice genetic diversity in East Kalimantan, because their existence only depends on traditional cultivation and conservation by local farmers based on needs and tendencies towards certain varieties. According to the current exploration study conducted in Penajam Paser Utara (PPU) and Paser, the smallest districts in East Kalimantan, there were high genetic diversities of rice existed in that two districts. As many as 71 local rice cultivars were collected, consisted of 53 rice and 18 glutinous rice. Traits characterization showed that there were large variation of plant height (66 to 209.33 cm), culm number (1 to 41.67), culm diameter (0.23 to 1.03 cm), leaf length (39 to 108.33 cm), leaf width (0.83 to 2.67 cm), leaf angle (10 to 50 degree), ligule length (11 to 55 mm) and weight of ten seeds (0.13 to 0.40 gram) in the local rice population showing high phenotypic variations of agro-morphological traits in the population. A strong negative correlation between culm number (tiller) and culm diameter, leaf length as well as leaf width was observed, which indicated that culm number is few if the culm diameter is big, and the leaves are longer and wider. Genetic diversity analysis based on Agro-morphological characters clustered the cultivars in nine and four classes for rice populations in PPU and Paser districts, respectively. Pre-identification of the local rice genetic potencies showed some superior and potential traits which will be very useful for rice breeding programs to develop new superior rice varieties